2006
DOI: 10.1111/j.1525-1438.2006.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Nerve-sparing class III radical hysterectomy: a modified technique to spare the pelvic autonomic nerves without compromising radicality

Abstract: The objectives were to describe our nerve-sparing class III radical hysterectomy technique and assess the feasibility and safety of the procedure as well as its impact on voiding function. From January to August 2005, 21 consecutive patients with FIGO stage IB-IIA cervical cancer and 1 patient with clinical stage II endometrial cancer underwent nerve-sparing radical hysterectomy with systematic pelvic lymphadenectomy. The transurethral catheter was removed on the seventh postoperative day. Then intermittent se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 29 publications
(61 reference statements)
1
30
0
1
Order By: Relevance
“…Various authors have established the feasibility of NSRH in stage IIa cervical cancers. 2,4,5,16,[22][23][24] Another drawback of L-NSRH is that it takes more time than conventional LRH. Our mean operative time is 88 minutes 11 for LRH and 160 minutes for L-NSRH.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have established the feasibility of NSRH in stage IIa cervical cancers. 2,4,5,16,[22][23][24] Another drawback of L-NSRH is that it takes more time than conventional LRH. Our mean operative time is 88 minutes 11 for LRH and 160 minutes for L-NSRH.…”
Section: Discussionmentioning
confidence: 99%
“…As a popular surgical technique sparing the pelvic autonomic nerves without compromising radicality, NSRH was reported to have similar clinical safety and extent of resection with RH for early stage cervical cancers treatment [33,37]. As Basaran and colleagues reported that there were neither adequate nor statistically relevant evidence addressing the oncologic safety of NSRH over that of RH, due to the scarcity and heterogeneity of effect estimates in different trials [8].…”
Section: Main Findingsmentioning
confidence: 99%
“…The return rate to normal voiding function post-operatively 14 and 21 days was 92.0% and 95.2%, respectively. Our laparoscopic nerve-sparing technique was comparable with open nerve-sparing radical hysterectomy in terms of early recovery of bladder function (Raspagliesi et al, Charoenkwan et al, 2006;Fujii et al, 2007b). In our opinion, previous cadaveric dissection and early recovery of postoperative bladder function could guarantee that suspected nerve fibers dissected via a laparoscopic approach were genuine nerve fibers.…”
Section: Discussionmentioning
confidence: 50%
“…The early clinical report for nerve-sparing radical hyster- (Trimbos et al, 2001). Most clinical reports have not described these veins (Raspagliesi et al, 2004;Katahira et al, 2005) or depicted them as the inferior vesical vein or the vesical veins without concrete information about the number of vesical veins (Sakuragi et al, 2005;Charoenkwan et al, 2006;Todo et al, 2006;Kato et al, 2007). Fujii S et al insisted that the vesical veins in the posterior leaf of the VUL consisted of middle and inferior vesical veins (Fujii et al, 2007a,b).…”
Section: Discussionmentioning
confidence: 96%